Exploring Challenge and Opportunities of Drug Formulation Manufacturers in Indonesia's Policy Shift - Nurfauzia, Amanda (Journal of Research in Social Science and Humanities, 2025)
Indonesia's pharmaceutical industry faces critical challenges due to its heavy reliance on imported Active Pharmaceutical Ingredients (APIs), which account for over 90% of total API use. This dependency creates inefficiencies, high costs, and vulnerabilities in supply chains, particularly during crises like the COVID-19 pandemic. To address this, the Indonesian government introduced the Change Source policy in 2022, aiming to enhance local production and reduce import dependency. This study explores the challenges and opportunities for drug formulation manufacturers amid this policy shift. Using a qualitative approach, data were gathered through in-depth interviews with four manufacturers and analysis of relevant regulations and secondary sources. Key challenges include high initial investment costs, inadequate infrastructure, and market demand uncertainties. However, opportunities arise from government incentives, increased local API demand, and innovation potential. Findings emphasize the importance of regulatory support, infrastructure development, and market assurance to foster sustainable growth in the pharmaceutical sector. By addressing these challenges, the policy has the potential to significantly boost Indonesia’s pharmaceutical self-reliance, reduce costs, and enhance resilience. This research provides a comprehensive understanding of the policy's impacts, offering valuable insights for policymakers and stakeholders in the pharmaceutical industry.